2007
DOI: 10.1159/000127385
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Baseline Clinical Predictive Factors of Response to Cetuximab-Irinotecan in Patients with Irinotecan-Refractory Metastatic Colorectal Cancer

Abstract: Objective: To identify easily available predictive factors of response to cetuximab-irinotecan in patients with irinotecan-refractory metastatic colorectal cancer. Methods: Retrospective analysis of patients treated with cetuximab (400 mg/m2 in week 1, 250 mg/m2 in subsequent weeks) plus irinotecan (180 mg/m2 every 2 weeks). We assessed demographic data, prior response to chemotherapy, number of metastatic sites, disease and metastatic disease durations, irinotecan-free interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The irinotecan-free interval is also available potential predictive factors. 21 , 22 And a correlation between irinotecan-free interval and survival outcomes was observed in the current study. Further investigation such as prospective, comparative cohort study is needed to clarify these prognostic factors.…”
Section: Discussionsupporting
confidence: 73%
“…The irinotecan-free interval is also available potential predictive factors. 21 , 22 And a correlation between irinotecan-free interval and survival outcomes was observed in the current study. Further investigation such as prospective, comparative cohort study is needed to clarify these prognostic factors.…”
Section: Discussionsupporting
confidence: 73%
“…Other retrospective studies found that EGFR expression was not associated with the efficacy of cetuximab [22] or panitumumab, another anti-EGFR monoclonal antibody [23]. Moreover, a recent prospective study found that cetuximab monotherapy was as effective in mCRC patients negative for EGFR as in those with EGFR IHC-positive disease, although patients were not selected based on KRAS mutation status in this previous study [24].…”
Section: Discussionmentioning
confidence: 77%
“…As reported in several clinical trials, EGFR status is not a reliable biomarker to select patients for cetuximab-based therapy. [43][44][45] KRAS, NRAS, and BRAF status are F I G U R E 6 Fibroblast growth factor receptor 4 (FGFR4) increases cell viability against epidermal growth factor receptor inhibition in colon cancer cells. A, Colon cancer cells with FGFR4 expression or vector control plasmid were treated with different concentrations of cetuximab (range, 31-500 μg/mL) for 48 h and cell viability were evaluated.…”
Section: Discussionmentioning
confidence: 99%